Continuous video-rate laser speckle imaging for intra- and postoperative cutaneous perfusion imaging of free flaps - Rauh, Annika; Henn, Dominic; Nagel, Sarah Sophie; Bigdeli, Amir Khosrow; Kneser, Ulrich; Hirche, Christoph (Journal of reconstructive microsurgery, 2019)
Background Success of free tissue transfer depends on standardized intraoperative flap design, microsurgical technique, and postoperative monitoring. We sought to investigate whether laser speckle imaging (LSI) is suitable for optimization of intraoperative flap design and postoperative monitoring of free flaps with skin paddles. Methods Skin perfusion was assessed with LSI in 27 free flaps after dissection at the donor site, after anastomosis at the recipient site, after inset and on postoperative days (POD) 1, 5, and 10. Skin perfusion of the whole flap (ROI [region of interest]-1) and the area over the pedicle (ROI-2) were compared between patients with and without postoperative complications (POC+ and POC − , respectively). A receiver operating characteristic (ROC) analysis was performed to determine the optimal cutoff for perfusion during LSI-guided microsurgery. Results In flaps without or only minor POC, intraoperatively measured perfusion over ROI-2 was significantly higher compared with ROI-1, whereas no significant differences were found for flaps with major POC. Perfusion of ROI-1 and 2 intraoperatively and on POD 1 was significantly lower in the POC+ compared with the POC− group (p < 0.05). ROC analysis yielded a threshold of 107 perfusion units (PU) at ROI-2 with an area under the curve (AUC) of > 0.8 for identification of flaps with major POC. Conclusion LSI is an easy to use, noninvasive technique for identification of malperfused areas in free flaps, thus allowing for intraoperative decision-making on flap dimensions and postoperative monitoring. LSI therefore is a valuable tool for perfusion assessment with a high potential to become an established part of microsurgical practice.